Design, personality traits and consumer responses to brand logos - Machado, Joana César (2019)
Despite the relevance of logos as communication cues, empirical studies of logo design issues in marketing journals are still scarce (Peterson et al., 2015). This study seeks to address this research gap by examining consumers’ responses to logo design, and specifically to the different types of natural designs, at a behavioral and psychological level. Additionally, we explore whether socio-demographic variables and consumer personality traits are sources of differences in such reactions.